2020
DOI: 10.1111/myc.13200
|View full text |Cite
|
Sign up to set email alerts
|

Candida spp. infective endocarditis: Characteristics and outcomes of twenty patients with a focus on injection drug use as a predisposing risk factor

Abstract: BackgroundCandida spp. infective endocarditis (CIE) although rare is associated with high morbidity and mortality. Risk factors include prosthetic heart valves and injection drug use (IDU). We reviewed all cases of CIE at our institution to describe the microbiology, treatment and outcomes of patients focusing on IDU as a predisposing factor.MethodsRetrospective cohort of patients with definite CIE between 2013 and 2019 at a university hospital was analysed. Demographic data collected included IDU, microbiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…is the causative pathogen of infection in patients with immunosuppressive conditions associated with chemotherapy or organ transplantation for malignant cancers and showed that the proportion of patients with solid or blood cancers and immunosuppressive status is higher among patients with Candida PB than among those with GPC PB and GNR PB [ 52 ]. In candidemia, the fungus spreads homogeneously, which can cause conditions such as IE [ 59 ], purulent spondylitis, and purulent arthritis [ 60 ]. Patients with candidemia are often in poor general condition because of immunosuppression or other reasons, so active source control such as debridement is often difficult.…”
Section: Resultsmentioning
confidence: 99%
“…is the causative pathogen of infection in patients with immunosuppressive conditions associated with chemotherapy or organ transplantation for malignant cancers and showed that the proportion of patients with solid or blood cancers and immunosuppressive status is higher among patients with Candida PB than among those with GPC PB and GNR PB [ 52 ]. In candidemia, the fungus spreads homogeneously, which can cause conditions such as IE [ 59 ], purulent spondylitis, and purulent arthritis [ 60 ]. Patients with candidemia are often in poor general condition because of immunosuppression or other reasons, so active source control such as debridement is often difficult.…”
Section: Resultsmentioning
confidence: 99%
“…IE due to candida species is relatively rare, accounting for around 2-4% of all cases [93,94]. Multiple outbreaks of disseminated candida infections have been traced back to using lemon juice as a solvent for intravenous heroin and cocaine [95][96][97].…”
Section: Candidamentioning
confidence: 99%
“…39 This is also endorsed by current guidelines, which only support a discontinuation of antifungal treatment if neutropenia has resolved. 17,18 Furthermore, in case of uncertain duration of ongoing candidemia, which is, for example typically the case in patients with intravenous drug use, the relative risk for occult metastatic infection sites or deep-seated tissue candidiasis 40,41 is elevated. Moreoever, it is also recommended to avoid treatment reducing in patients with suppurative thrombophlebitis, pacemakers, intraventricular devices and endovascular prostheses.…”
Section: Limitations To Treatment Shortening Strategiesmentioning
confidence: 99%